Exhaled nitric oxide concentration in the period of 60 min after submaximal exercise in the cold. (10th October 2014) - Stensrud, Trine; Stang, Julie; Thorsen, Einar; Bråten, Veslemøy
Summary: Background: Fractional expired nitric oxide (FENO ) is decreased after exercise. The effect of exercise in the cold upon FENO is unknown. Purpose: To examine changes in FENO after a short, high intensive exercise test in a cold and in a temperate environment. Methods: Twenty healthy well‐trained subjects (eight females) aged 18–28 years performed an 8‐min exercise test at 18°C (SD = 1.0) and −10°C (SD = 1.2) ambient temperature. The tests were performed in a climate chamber in random order. The workload corresponded to 90–95% of peak heart rate (HRpeak ) during the last 4 min. FENO was measured offline. Exhaled gas was sampled in Mylar ® bags using a collector kit with a flow restrictor and analysed within 2 h. FENO was measured before exercise and repeatedly during the first hour after. ANOVA for repeated measures was used to compare differences in FENO after exercise between environments. Results: There was no difference in baseline FENO . A significant difference in FENO between environments was found after warm‐up and from 20 to 30 min after exercise, with FENO being lower after exercise in the cold ( P <0.05). The maximal reduction in FENO was seen 5 min after exercise and was not different between environments. Conclusion: Recovery of FENO was slower after exercising in −10°C compared with 18°C.